Ketika Dakwah Bertemu Teknologi Ikhtiar Menjaga Akal Sehat Di Era Digital - Lismawati Lismawati; Masduki Asbari; Hikmatis Jum'a; Yulia Wulandari (AGUSPATI RESEARCH INSTITUTA, 2025)
knowledge in the 9th century in Baghdad. This report is based on an oral story from the Gita Wirjawan channel entitled